Fragmentation of Civil Law and the Crisis of Legal Certainty in the Era of Globalization Based on an Analysis of the Urgency of Establishing International Civil Law in Indonesia - Siti Chadijah; Muhammad Rifqi Rifa'i; Lulu Syakirah Alatas; Sheilly Hawaningsih; Niken Ayu Wulandari (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the fragmentation of civil law and its impact on legal certainty in Indonesia amid the growing complexity of cross-border legal relations in the era of globalization. The research focuses on the urgency of establishing an integrated Private International Law framework to address inconsistencies within the national legal system. Using a normative juridical method with statutory and conceptual approaches, this study analyzes the coexistence of colonial legal heritage, national regulations, and inconsistent judicial practices that contribute to legal fragmentation. The findings show that the absence of a comprehensive codification of Private International Law creates uncertainty in determining applicable law, jurisdiction, and recognition of foreign judgments in civil disputes involving foreign elements. This condition weakens the consistency and predictability of legal enforcement. Therefore, the study concludes that the establishment of a codified and integrated Private International Law system is urgently needed to strengthen legal certainty and support the harmonization of Indonesia’s national legal system in responding to globalization. Studi ini meneliti fragmentasi hukum perdata dan dampaknya terhadap kepastian hukum di Indonesia di tengah meningkatnya kompleksitas hubungan hukum lintas batas di era globalisasi. Penelitian ini berfokus pada urgensi pembentukan kerangka Hukum Perdata Internasional yang terintegrasi untuk mengatasi inkonsistensi dalam sistem hukum nasional. Dengan menggunakan metode yuridis normatif dengan pendekatan hukum statutori dan konseptual, studi ini menganalisis koeksistensi warisan hukum kolonial, peraturan nasional, dan praktik peradilan yang tidak konsisten yang berkontribusi pada fragmentasi hukum. Temuan menunjukkan bahwa tidak adanya kodifikasi Hukum Perdata Internasional yang komprehensif menciptakan ketidakpastian dalam menentukan hukum yang berlaku, yurisdiksi, dan pengakuan putusan asing dalam sengketa perdata yang melibatkan unsur asing. Kondisi ini melemahkan konsistensi dan prediktabilitas penegakan hukum. Oleh karena itu, studi ini menyimpulkan bahwa pembentukan sistem Hukum Perdata Internasional yang terkodifikasi dan terintegrasi sangat dibutuhkan untuk memperkuat kepastian hukum dan mendukung harmonisasi sistem hukum nasional Indonesia dalam menanggapi globalisasi.